2010
DOI: 10.1007/s12144-010-9075-9
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Work-Family Conflict? The Function of Work Support and Working from Home

Abstract: The current study examined how work support resources and working from home influenced forms of work-family conflict (WFC) in employees at a large corporation. Scales measuring employee's general WFC, time-based WFC, and strainbased WFC were used to evaluate the extent to which employees experienced workinduced conflict at home. Two forms of working at home were assessed, days worked at home and extra hours worked at home, and five variables measured the extent of one's support resources: work social support, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…Job resources (support from supervisors, co-workers, family-friendly policies and job autonomy) were negatively related to WFC. In other words, job resources could act as buff ers to work-family confl ict; similar to previous fi ndings (e.g: Dinger, Thatcher & Stepina, 2010;Eng, Moore, Grunberg, Greenberg, & Sikora, 2010). Having supportive supervisors and co-workers improve the employee's ability to respond eff ectively to multiple role demands and thereby decrease their perception of WFC.…”
Section: Discussionsupporting
confidence: 79%
“…Job resources (support from supervisors, co-workers, family-friendly policies and job autonomy) were negatively related to WFC. In other words, job resources could act as buff ers to work-family confl ict; similar to previous fi ndings (e.g: Dinger, Thatcher & Stepina, 2010;Eng, Moore, Grunberg, Greenberg, & Sikora, 2010). Having supportive supervisors and co-workers improve the employee's ability to respond eff ectively to multiple role demands and thereby decrease their perception of WFC.…”
Section: Discussionsupporting
confidence: 79%
“…Compared with adding extra resources which are costly to implement (e.g., work-family policies), we shed light on the necessity to optimize social support per se. We argue that utilizing support from work domain can reduce work-to-family conflict (Cheuk and Wong 1995;Cohen and Wills 1985;Eng et al 2010). Importantly, we suggest that activating employees' intrinsic motivation to learn from received support for work-to-family facilitation can also strenthen employees' positive evaluation towards organizations.…”
Section: Introductionmentioning
confidence: 79%
“…However, even though men and women seem to differ in their sources of social support, both benefit from this support in reducing work-family imbalance and conflict (McMullan et al, 2018;van Daalen et al, 2006). While some research (Eng, Moore, Grunberg, Greenberg, & Sikora, 2010;Julien, Somerville, & Culp, 2011) has concluded that social support at work reduces WFC and social support at home reduces family-work conflict for women, other research determined that only social support at home reduce family-work conflict (Liao, 2011;van Daalen et al, 2006).…”
Section: Work-life Balance For Women Leadersmentioning
confidence: 99%